Initial Clinical Experience with Percutaneous Endocardial Septal Pulsed Field Ablation in Hypertrophic Obstructive Cardiomyopathy: A First-in-Human Case Series - Haoruo Zhang; Yanfeng Tian; Songqing Yang; Rui Cao; Haoran Jing; Chunlin Gong; Jiaoyue Zhong; Yuran Chen; Siting Hong; Zhaojun Wang (Journal of Clinical Medicine, 2026)
Background: Pulsed field ablation is a nonthermal ablation modality with a potentially favorable tissue selectivity profile. However, its application in septal reduction therapy for hypertrophic obstructive cardiomyopathy remains unexplored clinically. We investigated the feasibility and short-term outcomes of percutaneous endocardial septal pulsed field ablation in patients with symptomatic hypertrophic obstructive cardiomyopathy. Methods: Five patients with symptomatic hypertrophic obstructive cardiomyopathy and persistent left ventricular outflow tract obstruction despite optimized conventional medical therapy underwent percutaneous endocardial septal pulsed field ablation guided by intracardiac echocardiography and 3-dimensional electroanatomical mapping. Results: Two-month follow-up data were available for all patients. Mean resting and provoked left ventricular outflow tract gradients decreased from 60.20 ± 14.10 and 93.60 ± 17.73 mmHg at baseline to 20.60 ± 5.18 and 27.80 ± 9.37 mmHg at 2 months, respectively. Improvements were also observed in systolic anterior motion, symptoms, 6 min walk distance, and Kansas City Cardiomyopathy Questionnaire score. One patient developed transient left bundle branch block and another transient complete atrioventricular block during the procedure; neither persisted. No persistent major procedure-related complications were observed during follow-up. Conclusions: In this small first-in-human case series, percutaneous endocardial septal pulsed field ablation was feasible and was associated with favorable short-term hemodynamic and clinical changes in selected patients with symptomatic hypertrophic obstructive cardiomyopathy. These findings are hypothesis-generating and require confirmation in larger studies with longer follow-up.